Review of the published literature to characterise clinical excellence in COVID-19 care. Issue 1165 (26th May 2021) - Garibaldi, Brian T; Chisolm, Margaret S; Berkenblit, Gail V; Feller-Kopman, David; Stephens, R Scott; Stewart, Rosalyn W; Wright, Scott M
Abstract: COVID-19 continues to be a major source of global morbidity and mortality. It abruptly stressed healthcare systems early in 2020 and the pressures continue. Devastating hardships have been endured by individuals, families and communities; the losses will be felt for years to come. As healthcare professionals and organisations stepped up to respond to the overwhelming number of cases, it is understandable that the focus has been primarily on coping with the quantity of the demand. During a pandemic, it is not surprising that few papers have drawn attention to the quality of the care delivered to those afflicted with illness. Despite the challenges, clinicians caring for patients with COVID-19 have risen to the occasion. This manuscript highlights aspirational examples from the published literature of thoughtful and superb care of patients with COVID-19 using an established framework for clinical excellence (formulated by the Miller-Coulson Academy of Clinical Excellence).